Ground Magnetic Surveying and Susceptibility Mapping Across Weathered Basalt Dikes Reveal Soil Creep and Pedoturbation - von Dobeneck, Tilo; Müller, Maximilian; Bosbach, Benjamin; Klügel, Andreas (Frontiers in Earth Science, 2021)
Ground magnetic survey profiles across a soil-covered and weathered mafic dike in sedimentary host rock not only permit to delineate the strike, width and burial depth of the intrusive basalt sheet, but also reflect the subsurface deformation of its clayey weathering products. We illustrate this finding and its practical geomorphological applicability by an example from the mid-German Heldburg Dike Swarm, where blue- and olive-gray basalt-derived clays inherited not just the dike space previously occupied by the basalt, but also large parts of its magnetic iron minerals and their strong induced and remanent magnetization. Such ductile basaltic ‘marker soils’ deform and move with the surrounding low-magnetic host soils, but remain distinguishable by their contrasting colors and high magnetic susceptibility. Ground magnetic surveys can therefore delineate soil creep distance at meter- and basalt weathering depth at decimeter-precision. Magnetic mapping of a weathered dike’s cross-section from an exploration trench by in-situ susceptometry permits to analyze past soil deformation in great detail. Weathering and solifluction transforms the simple ‘vertical sheet’ anomalies of dikes into complex, but still interpretable composite patterns, providing a new and promising exploratory approach for field studies concerned with soil creep and pedoturbation.